(untitled) (Innovaciones Educativas, 2022)
Technological progress brought advantages and disadvantages in the academic field, allowing students and professors to access extensive specialized information. Among the disadvantages are plagiarism, copying, and other similar actions. As a matter of fact, academic plagiarism is the most frequent dishonest practice among students in the world. In this regard, the inquiries in this area are multiple and from different theoretical approaches. The Ibero-American level, Sureda, Comas and Urbina, (2005) and Comas-Forgas and Sureda-Negre (2010) are pioneering studies in the field. In this framework, this research aims to compare the awareness, prevalence, and assessment of dishonest practices by students entering the university of the disciplines of Arts and Humanities (Peru) and Health Sciences (Chile). A quantitative descriptive with a non-experimental and cross-sectional design method was used. Our sample considered 217 participants to whom a previously validated questionnaire was applied. After the analysis, results show that awareness of plagiarism and references do not differ between both fields of knowledge. Most of them present similar data in terms of prevalence and assessment, except for specific actions and practices whose sanction could be more regulated by legal bodies.